PENGARUH METAN (MEDIA TANAM ORGANIK TERHADAP PERTUMBUHAN KAKTUS (Gymnocalycium damsii) - Tanjung, Indayana Febriani; Adisti, Yuda; Atika, Dewi Nurul (BIOEDUKASI (Jurnal Pendidikan Biologi), 2023)
One of the factors that influence plant growth and development is the use of planting media. In this study, we will provide information on the use of suitable planting media for cactus (Gymnocalycium damsii) in various treatments of using growing media including compost, cocopite, roasted husks and sand, which were compared to 7 treatments. This research was conducted in October 2022 using the experimental trial method on observations made for 3 weeks. The tools used include soil testers, calipers, scales, planting media cups. The purpose of this research was to find out the use of planting media that is suitable for the growth and development of cactus (Gymnocalycium damsii). The results found that the use of planting media III with a composition (husk 25 gr + compost 150 gr + sand 25 gr) that gives a diameter development of 1.1 inches and a significant growth to the length of the cactus roots in the use of planting medium II with a composition (husk 25 gr + compost 75 gr + sand 100 gr) ) which provides an average growth addition of root length growth of 0.5 cm.             Kata kunci:  Media Tanam, Pertumbuhan, Gymnocalycium damsii